Price Competition in an Inflationary Environment - Peter Duersch; Thomas Eife (University of Heidelberg, Department of Economics, 2013)
We study how inflation and deflation affect firms' ability to cooperate in an experimental Bertrand duopoly with differentiated products. We find that there is significantly less cooperation in the treatments with inflation and deflation compared to the no-inflation treatments. The difficulties to cooperate affect prices and welfare: Depending on the market structure, inflation and deflation lead to significantly lower (real) prices and higher welfare.
urn:nbn:de:bsz:16-heidok-153258
Keywords: 330; Bertrand Duopoly; Inflation; Experiment; Money Illusion